Case report: Immune modulation after PD-1 inhibitor therapy in a patient with extranodal NK/T-cell lymphoma secondary to chronic active Epstein-Barr virus disease unveiled by single-cell transcriptomics - Wang, Yao; Zhang, Minan; Xue, Qingfeng; Zhou, Huan; Chen, Jie; Wang, Hong; Zhang, Yaping; Shi, Wenyu (Frontiers in Immunology, 2023)
Chronic active Epstein-Barr virus disease (CAEBV) is a systemic lymphoproliferative disorder that is closely linked to Epstein-Barr virus (EBV) infection. The clinical course and severity of CAEBV can vary, and in some cases, it can progress to overt lymphoma, which is characterized by extranodal natural killer/T-cell lymphoma and has a poor clinical outcome. Although anti-programmed cell death protein-1 (PD-1) therapy has shown effectiveness in some patients with EBV-associated disease, it has been less successful in others, and the exact mechanism of action of PD-1 inhibitor therapy in these diseases remains unclear. In this report, we describe a patient who was diagnosed with extranodal natural killer/T-cell lymphoma secondary to CAEBV and experienced rapid disease progression accompanied by hemophagocytic lymphohistiocytosis after receiving PD-1 inhibitor therapy. Single-cell RNA sequencing revealed a significant increase in the patient's lymphocyte count, especially in natural killer cells, with increased activity following PD-1 inhibitor therapy. This case raises questions about the efficacy and safety of PD-1 inhibitor therapy in patients with EBV-associated diseases.